2010
DOI: 10.1007/s11270-010-0394-0
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Studies on Atrazine Effects on Human Intestinal Cells

Abstract: Considering the importance of the oral route for human exposure to atrazine, we have investigated the possible effect of this herbicide on the human intestinal cells and the integrity of the epithelial barrier, using Caco-2 cells as the intestinal model in vitro. We evaluated possibile cytotoxic and genotoxic effects of atrazine in concentrations ranging from 1 to 250 μM on the Caco-2 cells at different stages of growth after short-and long-term exposure. Results from the tetrazolium blue (MTT) test and the Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Because the concentration of ATZ used in the present study were higher than those reported for other cells 7,9,15 and similar to that used in the Caco-2 cells, 16 we think that Leydig cell effect may not be an important component of ATZ toxicity. The results showed that Kol had no deleterious effects on Leydig cell viability as demonstrated in the MTT assay.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Because the concentration of ATZ used in the present study were higher than those reported for other cells 7,9,15 and similar to that used in the Caco-2 cells, 16 we think that Leydig cell effect may not be an important component of ATZ toxicity. The results showed that Kol had no deleterious effects on Leydig cell viability as demonstrated in the MTT assay.…”
Section: Discussionmentioning
confidence: 46%
“…14 Moreover, ATZ affects cell growth, proliferation, and differentiation in several experimental models exposed to ATZ in vitro. 9,15,16 In the present study, the toxicity of ATZ was further investigated using a ILC culture model. Kol, because of its antioxidant properties, was chosen to examine its attenuating effect on cytotoxicity caused by ATZ.…”
Section: Introductionmentioning
confidence: 99%
“…Mentioned above, atrazine is noted as one of the most used herbicides worldwide; its presence has been confirmed in air, fog, ice, seawater, freshwater and rain [ 9 , 10 ]. Concerning its effect on human health, atrazine acts as a potential endocrine disruptor [ 10 , 11 ], modulates the cell cycle and the cell growth, affects the intestinal epithelium transport regulation, and presents liver cytotoxicity and genotoxicity [ 10 , 12 , 13 , 14 , 15 ]. These reasons were behind the ban applied by the European Union to this chemical in 2004 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that atrazine has potential biological toxicity. Some studies have shown that exposure to atrazine may cause physiological disorders of humans and animals [4,5]. Therefore, there is a need for monitoring atrazine residue levels.…”
Section: Introductionmentioning
confidence: 99%